Efficient composite heat exchange tube with synergistic corrosion prevention and heat conduction functions and preparation method of efficient composite heat exchange tube
By designing a multi-layer shielding and anti-corrosion system on the heat exchange tube, including thermally conductive anti-corrosion coating, thermally conductive oil or thermally conductive grease layer and low-surface energy resin tube, the problem of insufficient anti-corrosion and thermal conductivity in corrosive media is solved, and the comprehensive performance of long-term anti-corrosion, thermal conductivity and anti-scale is achieved.
Patent Information
- Application Number
- CN202411991463.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-15
AI Technical Summary
Existing heat exchange pipes are prone to corrosion and leakage when facing corrosive media, and the coating anti-corrosion methods have problems of shedding and thermal resistance, making it difficult to achieve comprehensive performance of long-term corrosion protection, thermal conductivity and scale prevention.
A multi-layer shielding and anti-corrosion system is adopted, including setting a thin and dense thermally conductive anti-corrosion coating on the outer layer of the metal tube, and adding thermal oil or thermally conductive grease layer between the coating and the resin tube. The fluidity of thermal oil or thermally conductive grease is used to eliminate thermal resistance of the air layer, combining high-thermal conductivity fillers such as graphene to improve thermal conductivity, and using low-surface energy fluororesin or silicone tubes on the outermost layer to prevent scaling.
It realizes long-term corrosion-proofing of the heat exchange tube, improves thermal conductivity, reduces coating thermal resistance, and enhances anti-scaling and condensation heat transfer performance, ensuring the long-term, stable and efficient operation of the heat exchange tube.
Smart Images

Figure HDA0005223742310000011 
Figure HDA0005223742310000012
Abstract
Description
Technical Field
[0001] The present invention relates to the field of heat exchange, and in particular to a high-efficiency composite heat exchange tube with coordinated anti-corrosion and heat conduction and a preparation method thereof, which is suitable for flue gas waste heat recovery. Background Art
[0002] As the core component of the heat exchange system, heat exchange tubes are widely used in many fields such as petroleum, chemical industry, electricity, refrigeration, aerospace, etc. In order to improve the heat exchange efficiency, heat exchange tubes are mostly made of metal materials such as stainless steel, copper, aluminum, etc., but when they encounter corrosive media, they are often prone to corrosion and leakage. The use of coating anti-corrosion is the most commonly used means to deal with such problems. However, due to the large differences in physical and chemical properties between polymer materials such as coatings and metal matrix materials, the coating is easily affected by various factors such as thermal expansion and contraction, stress, fluid erosion, etc. as the service time increases, and it falls off, thereby losing its protective effect on the metal matrix. Compounding a layer of resin tube on the outside of the metal tube to isolate the corrosive medium from the metal tube is another method to prevent corrosion of the metal tube [invention patent CN112781410A]. The advantage of this metal surface composite resin tube method is that it solves the problem of anti-corrosion coating falling off. Its disadvantages are: due to the poor density of the resin tube, when the composite resin tube is thin, its air permeability and water permeability are high, and the protection performance of the metal tube is limited [Corrosion Science, 2023, 218: 111141]; when the resin tube is thicker, the thermal resistance is large and the heat transfer performance is greatly affected. In addition, due to the uneven surface of the metal tube, it often leads to the existence of an air layer at the interface between the two phases when it is coupled with the resin tube. Because the thermal conductivity of the air layer is very low, only 0.025W / (m·K), it will greatly reduce the heat transfer efficiency of the heat exchange tube. In addition, scaling on the surface of the heat exchange tube is another major reason for the low heat transfer efficiency of existing heat exchange tubes.
[0003] In summary, how to achieve that the heat transfer tube has excellent anti-corrosion performance while also having efficient heat conduction and anti-scaling performance and maintaining long-term effectiveness is a major problem in this field. Summary of the invention
[0004] The purpose of the present invention is to provide a high-efficiency composite heat exchange tube with long-term anti-corrosion, heat conduction and anti-scaling functions.
[0005] The technical solution of the present invention is a high-efficiency composite heat exchange tube with synergistic anti-corrosion and heat conduction, characterized in that: the mother tube is a metal tube, the outermost layer is a resin tube, and a thin and dense heat-conductive anti-corrosion coating is provided between the resin tube and the mother tube.
[0006] Furthermore, a layer of heat-conducting oil liquid is contained between the heat-conducting anti-corrosion coating and the resin pipe.
[0007] Alternatively, the thermal oil may be replaced by thermal grease.
[0008] Furthermore, the heat-conducting oil includes one of the following types: mineral heat-conducting oil and synthetic heat-conducting oil; the thermal grease includes one of the following types: silicone oil-based thermal grease and non-silicone polymer-based thermal grease.
[0009] Furthermore, the heat transfer oil includes three categories (GB23971-2009) of heat transfer oil: L-QB, L-QC or L-QD.
[0010] Based on the fluidity of the heat-conducting oil or grease layer, the solid-solid contact thermal resistance and the air layer thermal resistance between the solid-solid two-phase interface can be eliminated, and at the same time, a liquid seal can be played on a small amount of corrosive molecules that pass through the surface resin tube layer.
[0011] Furthermore, the thermal conductive anti-corrosion coating and the thermal conductive oil or thermal conductive grease layer contain fillers that can synergistically improve the thermal conductivity and anti-corrosion properties, and the content of the fillers is 5-20wt.%, so as to increase the density and thermal conductivity of the coating, so that the coating and the liquid oil film layer have good shielding and anti-corrosion properties without needing to be very thick, thereby reducing the additional thermal resistance caused by the increase in coating thickness.
[0012] Optionally, the thermally conductive and anti-corrosion filler is preferably one or a combination of graphene, fluorinated graphene, carbon nanotubes, and micro-nano graphite powder.
[0013] Furthermore, the thermally conductive anti-corrosion coating includes one of epoxy resin, modified epoxy resin, polyurethane, and silicone resin.
[0014] Furthermore, the outermost resin tube is one of a fluororesin tube or a silicone tube with low surface energy properties to achieve anti-scaling, functional corrosion protection and enhanced condensation heat transfer, preferably one of polytetrafluoroethylene (PTFE), polyperfluoroethylene propylene (FEP), tetrafluoroethylene-perfluoropropyl vinyl ether copolymer (PFA), tetrafluoroethylene and ethylene copolymer (FS-40), polyalkyl silicone resin, polyaryl silicone resin, and polyalkylaryl silicone resin.
[0015] Alternatively, the fluororesin tube or silicone resin tube may be replaced by a common resin tube with a layer of fluorine or silicon element sputtered on the outer surface thereof.
[0016] Furthermore, the total thickness of the thermal conductive anti-corrosion coating, liquid layer and resin tube layer on the surface of the metal mother tube is not more than 300 μm, wherein the thickness of the thermal conductive anti-corrosion coating is 100-150 μm, the thickness of the liquid layer is 5-20 μm, and the thickness of the resin tube layer is 100-150 μm.
[0017] Furthermore, the metal pipe is made of one of carbon steel, stainless steel, copper and aluminum alloy.
[0018] The preparation method and steps of a high-efficiency composite heat exchange tube with synergistic anti-corrosion and heat conduction described in the present invention are as follows:
[0019] (1) First, the base metal tube is sandblasted;
[0020] (2) Applying thermal conductive anti-corrosion coating;
[0021] (3) Apply thermal oil or thermal grease;
[0022] (4) After the resin is extruded through a die or coated with a thin-walled sheath, the resin tube and the mother tube are tightly combined by heating and welding. Furthermore, in step (4), the heating temperature during the heating and welding process needs to be appropriately increased and the insulation time needs to be extended. The heating temperature is 100-400°C; the insulation time is 5-60 minutes.
[0023] Compared with the prior art, the present invention has the following significant advantages: (1) Based on the preparation process characteristics of the coating and the resin tube and their influence on the microstructure and density of the material, a multi-layer shielding and anti-corrosion system of the coating and the resin tube is prepared, which overcomes the shortcomings of poor adhesion and easy detachment of a single coating and poor density and poor anti-permeability of a single resin tube layer, and synergistically solves the problems of long-term corrosion protection of the heat exchange tube and high thermal resistance of the coating. (2) A layer of heat-conducting oil or heat-conducting grease is also designed between the coating and the resin tube, and its good fluidity is used to eliminate the thermal resistance of the air layer and the contact thermal resistance between the solid-solid phases, thereby minimizing the thermal resistance of the coating of the heat exchange tube and improving the shielding and anti-corrosion performance. (3) Graphene (5300W / (m·K)) filler with a two-dimensional structure and high thermal conductivity is further added to the coating, and the anti-corrosion and thermal conductivity of the heat exchange tube are greatly improved by constructing a maze effect and a three-dimensional thermal conductive network. (4) The outermost resin tube is preferably a fluororesin tube or a silicone resin tube with low surface energy properties, or a fluorine- or silicon-containing low-energy surface material is prepared on the outer surface of other resin tubes to improve the anti-scaling, anti-corrosion and condensation heat transfer performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a diagram of the contact process between a water droplet and the surface of Example 2;
[0025] Figure 2 (a) is the surface condensation state diagram of Example 2; (b) is the surface condensation state diagram of Comparative Example 3. DETAILED DESCRIPTION
[0026] In order to provide a further understanding of the present invention, the present invention is further described below in conjunction with specific implementation examples.
[0027] Embodiment 1:
[0028] (1) Substrate and pretreatment:
[0029] Take a copper heat exchange tube with a size of Φ16mm*2mm*1m, and use quartz sand with a particle size of 0.5mm to sandblast the surface to remove the oxide film on the surface of the heat exchange tube. Soak the sandblasted heat exchange tube in alkaline degreasing liquid for 10 minutes to remove surface grease and residues, and then rinse it with deionized water to ensure that there is no oil film remaining on the surface. Immerse the degreased heat exchange tube in 10wt.% nitric acid for 3 minutes to further remove fine oxides and activate the metal surface. After activation, rinse it thoroughly with deionized water to ensure that the surface is clean and free of dirt.
[0030] (2) Thermal conductive anti-corrosion layer:
[0031] On the surface of the pre-treated heat exchange tube, a layer of DH22-2 modified epoxy heat exchanger special coating with thermal conductive anti-corrosion filler is evenly applied by brushing. The thermal conductive anti-corrosion filler added is graphene, accounting for 10wt.%. The coating thickness is controlled at 100μm. The brushing process ensures that the coating surface is uniform, free of bubbles and sagging. After the coating is dry at room temperature, it is baked at 170℃ for 2 hours to complete the final curing.
[0032] (3) Thermal oil layer:
[0033] A layer of L-QD350 heat-conducting oil is applied on the surface of the heat-conducting anti-corrosion coating. Graphene filler is added to the heat-conducting oil. The filler ratio is 10wt.%. The heat-conducting oil is evenly applied with a thickness of 10μm.
[0034] (4) Outer resin tube layer:
[0035] The PFA resin is coated on the surface of the heat exchange tube by extrusion process and heating welding. The heating temperature is 330℃, the time is 10 minutes, and the thickness of the extruded layer is 100μm, ensuring that there are no defects such as bubbles and delamination. At this time, the outermost layer is a low-energy surface containing fluorine elements, and no subsequent magnetron sputtering treatment is required.
[0036] Embodiment 2:
[0037] (1) Substrate and pretreatment:
[0038] Take a Q235 carbon steel heat exchange tube with a size of Φ18mm*2mm*1m, and use quartz sand with a particle size of 0.5mm to sandblast the surface to remove the oxide film on the surface of the heat exchange tube. Soak the sandblasted heat exchange tube in alkaline degreasing liquid for 10 minutes to remove surface grease and residues, and then rinse it with deionized water to ensure that there is no oil film remaining on the surface. Immerse the degreased heat exchange tube in 10wt.% sulfuric acid for 3 minutes to further remove fine oxides and activate the metal surface. After activation, rinse it thoroughly with deionized water to ensure that the surface is clean and free of dirt.
[0039] (2) Thermal conductive anti-corrosion layer:
[0040] On the surface of the pre-treated heat exchange tube, a layer of epoxy coating with thermal conductive anti-corrosion filler is evenly applied by spraying. The thermal conductive anti-corrosion filler is fluorinated graphene, accounting for 10wt.%. The coating thickness is controlled at 150μm, and the brushing process ensures that the coating surface is uniform, free of bubbles and sagging. After the coating is dry at room temperature, it is baked at 60℃ for 3 hours to complete the final curing.
[0041] (3) Thermal grease layer:
[0042] A layer of silicone oil-based thermal grease is applied on the surface of the thermal conductive anti-corrosion coating. Fluorinated graphene filler is added to the thermal grease. The filler ratio is 10wt.%. The thermal grease is evenly applied with a thickness of 20μm.
[0043] (4) Outer resin tube layer:
[0044] On the surface of the thermal grease layer, a layer of epoxy resin tube is compounded by extrusion and heating welding. The heating temperature is 140°C, the time is 20 minutes, and the thickness is 120μm, ensuring that there are no defects such as bubbles and unevenness.
[0045] (5) Surface modification of the outermost resin tube:
[0046] Using polytetrafluoroethylene as the target material, magnetron sputtering technology was used to modify the outermost layer of the composite tube. The thickness of the modified layer was precisely controlled to be 100nm by adjusting the sputtering parameters.
[0047] Embodiment 3:
[0048] (1) Substrate and pretreatment:
[0049] Take a 1060 aluminum alloy heat exchange tube with a size of Φ14mm*2mm*1m, and use quartz sand with a particle size of 0.2mm to sandblast the surface to remove the oxide film on the surface of the heat exchange tube. Soak the sandblasted heat exchange tube in anhydrous ethanol for 10 minutes to remove surface grease and residue. Immerse the degreased heat exchange tube in 10wt.% hydrochloric acid for 3 minutes to further remove fine oxides and activate the metal surface. After activation, rinse thoroughly with deionized water to ensure that the surface is clean and free of dirt.
[0050] (2) Thermal conductive anti-corrosion layer:
[0051] On the surface of the pre-treated heat exchange tube, a layer of polyurethane coating with thermal conductive anti-corrosion filler is evenly applied by spraying. The thermal conductive anti-corrosion filler is carbon nanotubes, accounting for 6wt.%. The coating thickness is controlled at 150μm, and the brushing process ensures that the coating surface is uniform, free of bubbles and sagging. After the coating is dry at room temperature, it is baked at 80℃ for 3 hours to complete the final curing.
[0052] (3) Thermal oil layer:
[0053] A layer of L-QD330 heat transfer oil is applied on the surface of the heat conductive anti-corrosion coating. Carbon nanotube filler is added to the heat transfer oil. The filler ratio is 6wt.%. The heat transfer oil is evenly applied with a thickness of 10μm.
[0054] (4) Outer resin tube layer:
[0055] On the surface of the heat transfer oil layer, a layer of polyimide tube is composited by coating and heating welding. The heating temperature is 300°C, the time is 20 minutes, and the thickness is 100μm, ensuring that there are no defects such as bubbles and unevenness.
[0056] (5) Surface modification of the outermost resin tube:
[0057] Using FEP as the target material, magnetron sputtering technology was used to modify the outermost layer of the composite tube. The thickness of the modified layer was precisely controlled to be 100nm by adjusting the sputtering parameters.
[0058] Embodiment 4:
[0059] (1) Substrate and pretreatment:
[0060] Take a 304 stainless steel heat exchange tube with a size of Φ16mm*2mm*1m, and use quartz sand with a particle size of 0.5mm to sandblast the surface to remove the oxide film on the surface of the heat exchange tube. Soak the sandblasted heat exchange tube in alkaline degreasing liquid for 10 minutes to remove surface grease and residues, and then rinse it with deionized water to ensure that there is no oil film remaining on the surface. Immerse the degreased heat exchange tube in 10wt.% nitric acid for 3 minutes to further remove fine oxides and activate the metal surface. After activation, rinse it thoroughly with deionized water to ensure that the surface is clean and free of dirt.
[0061] (2) Thermal conductive anti-corrosion layer:
[0062] On the surface of the pre-treated heat exchange tube, a layer of organic silicon coating with thermal conductive anti-corrosion filler is evenly applied by brushing. The thermal conductive anti-corrosion filler is micro-nano graphite powder, accounting for 10wt.%. The coating thickness is controlled at 150μm. The brushing process ensures that the coating surface is uniform, free of bubbles and sagging. After the coating is dry at room temperature, it is baked at 140℃ for 2 hours to complete the final curing.
[0063] (3) Thermal oil layer:
[0064] A layer of L-QD340 heat-conducting oil is applied on the surface of the heat-conducting anti-corrosion coating. Nano graphite powder filler is added to the heat-conducting oil. The filler ratio is 10wt.%. The heat-conducting oil is evenly applied with a thickness of 10μm.
[0065] (4) Outer resin tube layer:
[0066] On the surface of the thermal oil layer, the silicone sheath is coated on the surface of the heat exchange tube by the coating method and heating and melting welding. The heating temperature is 320℃, the time is 10 minutes, and the thickness is 100μm, ensuring that there are no defects such as bubbles and delamination. At this time, the outermost layer is a low-energy surface containing silicon elements, and no subsequent magnetron sputtering treatment is required.
[0067] Comparative Example 1:
[0068] (1) Substrate and pretreatment:
[0069] Take a Q235 carbon steel heat exchange tube with a size of Φ18mm*2mm*1m, and use quartz sand with a particle size of 0.5mm to sandblast the surface to remove the oxide film on the surface of the heat exchange tube. Soak the sandblasted heat exchange tube in alkaline degreasing liquid for 10 minutes to remove surface grease and residues, and then rinse it with deionized water to ensure that there is no oil film remaining on the surface. Immerse the degreased heat exchange tube in 10wt.% sulfuric acid for 3 minutes to further remove fine oxides and activate the metal surface. After activation, rinse it thoroughly with deionized water to ensure that the surface is clean and free of dirt.
[0070] (2) Thermal conductive anti-corrosion layer:
[0071] On the surface of the pre-treated heat exchange tube, a layer of epoxy coating with thermal conductive anti-corrosion filler is evenly applied by spraying. The thermal conductive anti-corrosion filler is fluorinated graphene, accounting for 10wt.%. The coating thickness is controlled at 290μm. The brushing process ensures that the coating surface is uniform, free of bubbles and sagging. After the coating is dry at room temperature, it is baked at 60℃ for 3 hours to complete the final curing.
[0072] Comparative Example 2:
[0073] (1) Substrate and pretreatment:
[0074] Take a Q235 carbon steel heat exchange tube with a size of Φ18mm*2mm*1m, and use quartz sand with a particle size of 0.5mm to sandblast the surface to remove the oxide film on the surface of the heat exchange tube. Soak the sandblasted heat exchange tube in alkaline degreasing liquid for 10 minutes to remove surface grease and residues, and then rinse it with deionized water to ensure that there is no oil film remaining on the surface. Immerse the degreased heat exchange tube in 10wt.% sulfuric acid for 3 minutes to further remove fine oxides and activate the metal surface. After activation, rinse it thoroughly with deionized water to ensure that the surface is clean and free of dirt.
[0075] (2) Thermal conductive anti-corrosion layer:
[0076] On the surface of the pre-treated heat exchange tube, a layer of epoxy coating with thermal conductive anti-corrosion filler is evenly applied by spraying. The thermal conductive anti-corrosion filler is fluorinated graphene, accounting for 10wt.%. The coating thickness is controlled at 150μm, and the brushing process ensures that the coating surface is uniform, free of bubbles and sagging. After the coating is dry at room temperature, it is baked at 60℃ for 3 hours to complete the final curing.
[0077] (3) Outer resin tube layer:
[0078] On the surface of the thermal grease layer, a layer of epoxy resin tube is compounded by extrusion and heating welding. The heating temperature is 140°C, the time is 20 minutes, and the thickness is 140μm, ensuring that there are no defects such as bubbles and unevenness.
[0079] (4) Surface modification of the outermost resin tube:
[0080] Using polytetrafluoroethylene as the target material, magnetron sputtering technology was used to modify the outermost layer of the composite tube. The thickness of the modified layer was precisely controlled to be 100nm by adjusting the sputtering parameters.
[0081] Comparative Example 3:
[0082] (1) Substrate and pretreatment:
[0083] Take a Q235 carbon steel heat exchange tube with a size of Φ18mm*2mm*1m, and use quartz sand with a particle size of 0.5mm to sandblast the surface to remove the oxide film on the surface of the heat exchange tube. Soak the sandblasted heat exchange tube in alkaline degreasing liquid for 10 minutes to remove surface grease and residues, and then rinse it with deionized water to ensure that there is no oil film remaining on the surface. Immerse the degreased heat exchange tube in 10wt.% sulfuric acid for 3 minutes to further remove fine oxides and activate the metal surface. After activation, rinse it thoroughly with deionized water to ensure that the surface is clean and free of dirt.
[0084] (2) Thermal conductive anti-corrosion layer:
[0085] On the surface of the pre-treated heat exchange tube, a layer of epoxy coating with thermal conductive anti-corrosion filler is evenly applied by spraying. The thermal conductive anti-corrosion filler is fluorinated graphene, accounting for 10wt.%. The coating thickness is controlled at 150μm, and the brushing process ensures that the coating surface is uniform, free of bubbles and sagging. After the coating is dry at room temperature, it is baked at 60℃ for 3 hours to complete the final curing.
[0086] (3) Thermal grease layer:
[0087] A layer of silicone oil-based thermal grease is applied on the surface of the thermal conductive anti-corrosion coating. The thermal grease contains fluorinated graphene filler, with a filler ratio of 10wt.%. The thermal grease is evenly applied with a thickness of 20μm.
[0088] (4) Outer resin tube layer:
[0089] On the surface of the thermal grease layer, a layer of epoxy resin tube is compounded by extrusion and heating welding. The heating temperature is 140°C, the time is 20 minutes, and the thickness is 120μm, ensuring that there are no defects such as bubbles and unevenness.
[0090] Comparative Example 4:
[0091] (1) Substrate and pretreatment:
[0092] Take a Q235 carbon steel heat exchange tube with a size of Φ18mm*2mm*1m, and use quartz sand with a particle size of 0.5mm to sandblast the surface to remove the oxide film on the surface of the heat exchange tube. Soak the sandblasted heat exchange tube in alkaline degreasing liquid for 10 minutes to remove surface grease and residues, and then rinse it with deionized water to ensure that there is no oil film remaining on the surface. Immerse the degreased heat exchange tube in 10wt.% sulfuric acid for 3 minutes to further remove fine oxides and activate the metal surface. After activation, rinse it thoroughly with deionized water to ensure that the surface is clean and free of dirt.
[0093] (2) Thermal grease layer:
[0094] A layer of silicone oil-based thermal grease is applied on the surface of the pretreated heat exchange tube. The thermal grease contains fluorinated graphene filler with a filler ratio of 10wt.%. The thermal grease is evenly applied with a thickness of 40μm.
[0095] (3) Outer resin tube layer:
[0096] On the surface of the thermal grease layer, a layer of epoxy resin tube is compounded by extrusion and heating welding. The heating temperature is 140°C, the time is 20 minutes, and the thickness is 250μm, ensuring that there are no defects such as bubbles and unevenness.
[0097] (4) Surface modification of the outermost resin tube:
[0098] Using polytetrafluoroethylene as the target material, magnetron sputtering technology was used to modify the outermost layer of the composite tube. The thickness of the modified layer was precisely controlled to be 100nm by adjusting the sputtering parameters.
[0099] Comparative Example 5:
[0100] (1) Substrate and pretreatment:
[0101] Take a Q235 carbon steel heat exchange tube with a size of Φ18mm*2mm*1m, and use quartz sand with a particle size of 0.5mm to sandblast the surface to remove the oxide film on the surface of the heat exchange tube. Soak the sandblasted heat exchange tube in alkaline degreasing liquid for 10 minutes to remove surface grease and residues, and then rinse it with deionized water to ensure that there is no oil film remaining on the surface. Immerse the degreased heat exchange tube in 10wt.% sulfuric acid for 3 minutes to further remove fine oxides and activate the metal surface. After activation, rinse it thoroughly with deionized water to ensure that the surface is clean and free of dirt.
[0102] (2) Outer resin tube layer:
[0103] On the surface of the thermal grease layer, a layer of epoxy resin tube is compounded by extrusion and heating welding. The heating temperature is 140°C, the time is 20 minutes, and the thickness is 290μm, ensuring that there are no defects such as bubbles and unevenness.
[0104] (3) Surface modification of the outermost resin tube:
[0105] Using polytetrafluoroethylene as the target material, magnetron sputtering technology was used to modify the outermost layer of the composite tube. The thickness of the modified layer was precisely controlled to be 100nm by adjusting the sputtering parameters.
[0106] The water contact angle of each embodiment was tested according to GB / T 30693-2014. Table 1 shows the water contact angle test results of embodiments 1-4. Figure 1 The figure is a diagram of the contact process between a water droplet and the surface of Example 2. It can be seen that although the water contact angles are all above 100°, the water contact angle of the silicone tube is smaller than that of the fluororesin tube, proving that the low surface energy property of the silicone tube is not as good as that of the fluororesin tube. Figure 1 It can be seen that it is difficult for water droplets to stay on the surface, showing good hydrophobicity. Table 2 shows the water contact angle test results of Comparative Examples 1-5. It can be seen that the contact angle of the surface treated by magnetron sputtering is higher, which indicates that magnetron sputtering post-treatment helps to improve the hydrophobicity of the surface, thereby causing droplet condensation and anti-scaling function on the surface. Figure 2 The surface condensation states of Example 2 and Comparative Example 3. It can be seen that the surface of Example 2 is a good droplet condensation mode, while the surface of Comparative Example 3 is a film condensation state. This shows that hydrophobicity also helps to improve the condensation heat transfer performance. The surface after magnetron sputtering has very low surface energy and strong hydrophobicity, so a good droplet condensation is formed on the surface.
[0107] Table 1 Water contact angle test results
[0108] Example 1 Example 2 Example 3 Example 4 Contact Angle 120.2° 140.6° 138.9° 115.8°
[0109] Table 2 Water contact angle test results
[0110] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Contact Angle 78.0° 140.6° 69.2° 140.3° 140.5°
[0111] The above four examples and five comparative examples were sampled, immersed, and tested for electrochemical AC impedance. The immersion environment was a 10wt.% dilute sulfuric acid solution at room temperature. Table 3 shows the Bode low-frequency modulus values of Examples 1-4 and Comparative Examples 1-5 after immersion for 3 days. It can be seen that the low-frequency modulus values of each example are maintained at 10 9 Ω·cm 2 In all comparative examples except comparative example 2, the low-frequency modulus values are all above 10 9 Ω·cm 2 Below, among them, the low frequency modulus value of comparative examples 1, 4, and 5 is already 10 6 Ω·cm 2 The following shows that the protective ability is lost. This shows that the preparation steps described in the present invention are indispensable, and the coating layer (i.e., the heat-conducting anticorrosive layer) and the resin layer alone cannot withstand long-term operation. After the two are combined, the heat exchange tube has the advantages of good anti-permeability, good hydrophobicity, and good thermal conductivity, ensuring the long-term stable and efficient operation of the heat exchange tube.
[0112] Table 3 Low frequency modulus test results
[0113] <![CDATA[Low-frequency modulus / (Ω·cm 2 )]]> Example 1 <![CDATA[6.7×10 9 ]]> Example 2 <![CDATA[4.6×10 9 ]]> Example 3 <![CDATA[2.8×10 9 ]]> Example 4 <![CDATA[5.3×10 9 ]]> Comparative Example 1 <![CDATA[7.7×10 5 ]]> Comparative Example 2 <![CDATA[5.0×10 9 ]]> Comparative Example 3 <![CDATA[8.7×10 7 ]]> Comparative Example 4 <![CDATA[6.8×10 5 ]]> Comparative Example 5 <![CDATA[1.3×10 5 ]]>
[0114] Since only comparative example 2 has protective performance, the thermal conductivity was tested after the protective layers of the above four embodiments and comparative example 2 were peeled off. Table 4 shows the test results of the thermal conductivity of the above four embodiments and comparative example 2. It can be seen that the thermal conductivity of comparative example 2 is significantly lower than that of each embodiment, which proves that the heat-conducting oil or thermal grease layer is indispensable. The heat-conducting oil and thermal grease layer eliminate the thermal resistance of the air layer and the contact thermal resistance between the solid-solid two phases by virtue of their good fluidity, thereby minimizing the thermal resistance of the coating of the heat exchange tube and improving the heat exchange efficiency.
[0115] Table 4 Thermal conductivity test results
[0116] Example 1 Example 2 Example 3 Example 4 Comparative Example 2 Thermal conductivity / (W / (m·K)) 0.568 0.581 0.546 0.604 0.280
[0117] The above description is only an embodiment of the present invention, which shows and describes the basic principles, main features and advantages of the present invention, and does not limit the patent scope of the present invention. It should be understood by those skilled in the art that the present invention is not limited by the above embodiments, and the above embodiments and descriptions only describe the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected, and the scope of protection claimed by the present invention is defined by the attached claims and their equivalents.
Claims
1. A high-efficiency composite heat exchange tube with synergistic anti-corrosion and heat conduction, characterized by: The mother tube is a metal tube, and the outermost layer is a resin tube. A thermal conductive anti-corrosion coating is provided between the resin tube and the mother tube, and a liquid layer is provided between the thermal conductive anti-corrosion coating and the resin tube. The liquid layer is thermal conductive oil or thermal conductive grease. Both the thermal conductive anti-corrosion coating and the liquid layer contain fillers that can synergistically improve the thermal conductivity and anti-corrosion performance.
2. The high-efficiency composite heat exchange tube with synergistic anti-corrosion and heat conduction as claimed in claim 1, characterized in that: The filler for synergistically improving thermal conductivity and anti-corrosion performance comprises at least one of graphene, fluorinated graphene, carbon nanotubes, and micro-nano graphite powder.
3. The high-efficiency composite heat exchange tube with synergistic anti-corrosion and heat conduction as claimed in claim 1, characterized in that: The filler content in the heat-conductive anti-corrosion coating or liquid layer is 5-20wt.%.
4. The high-efficiency composite heat exchange tube with synergistic anti-corrosion and heat conduction as claimed in claim 1, characterized in that : The outermost resin tube is one of a fluororesin tube and a silicone resin tube.
5. A high-efficiency composite heat exchange tube with synergistic anti-corrosion and heat conduction as claimed in claim 1, characterized in that The outermost resin tube material includes one of the following resins: polytetrafluoroethylene PTFE, polyperfluoroethylene propylene FEP, tetrafluoroethylene-perfluoropropyl vinyl ether copolymer PFA, tetrafluoroethylene and ethylene copolymer FS-40, polyalkyl silicone resin, polyaryl silicone resin, polyalkylaryl silicone resin.
6. The high-efficiency composite heat exchange tube with synergistic anti-corrosion and heat conduction as claimed in claim 1, characterized in that: The specific preparation steps are as follows: (1) First, the base metal tube is sandblasted; (2) Applying thermal conductive anti-corrosion coating; (3) Apply thermal oil or thermal grease; (4) The resin is extruded through a die or coated and then heated and welded to tightly bond the resin tube to the mother tube.
7. A high-efficiency composite heat exchange tube with synergistic anti-corrosion and heat conduction as claimed in claim 1, characterized in that: The total thickness of all protective layers on the surface of the metal tube is no more than 300 μm.
8. The high-efficiency composite heat exchange tube with synergistic anti-corrosion and heat conduction as claimed in claim 1, characterized in that: A layer of low-energy surface material containing fluorine or silicon elements is prepared on the outer surface of the outermost resin tube by using a measurement and control sputtering method.
9. The high-efficiency composite heat exchange tube with synergistic anti-corrosion and heat conduction as claimed in claim 1, characterized in that: The heat-conducting oil includes one of the following types: mineral heat-conducting oil and synthetic heat-conducting oil; the thermal grease includes one of the following types: silicone oil-based thermal grease and non-silicone polymer-based thermal grease.
10. The high-efficiency composite heat exchange tube with synergistic anti-corrosion and heat conduction as claimed in claim 1, characterized in that: The heat transfer oil is L-QB, L-QC or L-QD type heat transfer oil.